Pola Pembinaan Narapidana Anak Oleh Lembaga Pembinaan Khusus Anak - Roroa, Lela Sari; Toule, Elsa Rina Maya; Latumaerissa, Denny (Faculty of Law Universitas Pattimura, 2025)
The government delegates the task of developing children to an organization called the Special Children's Correctional Institution (hereinafter referred to as LPKA). LPKA is a place to educate and guide children who are detained or have committed violations of the law. Forms of guidance for child prisoners at LPKA Class II Ambon include: personality development, skills development, and formal and non-formal education. So, through the coaching carried out, it is hoped that when the child returns to society, the child will have self-confidence and will always have the energy to act positively. However, based on the reality in LPKA Class II Ambon, through the existing forms of coaching, there is still no influence on the results of coaching the target children, because when the children return to society, the children do not have self-confidence and no energy to act positively. The legal research method used is normative legal research or library legal research, this is legal research that examines document studies, namely using various primary legal materials such as statutory regulations, court decisions, legal theories, and can be in the form of expert opinions. From the results of research conducted by researchers using conceptual and statutory approaches, the results concluded are that in the problem of coaching patterns at the Ambon Class II Special Child Development Institute (LPKA) it can be said that there is significantly no influence when children return to living their lives in social environment of society. The factors that hamper the implementation of training for child prisoners at LPKA are: LPKA facilities do not fully support the pattern of training for children of prisoners, such as limited skills space, lack of skills tools, lack of tables and chairs.